Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1017/s1742170508002299
|View full text |Cite
|
Sign up to set email alerts
|

Economizing the use of nitrogen fertilizer in wheat production through enriched compost

Abstract: Manipulation of organic wastes and their composts as a source of organic matter (OM) and nutrients is imperative for sustainable agriculture. Further, the fortification of composts with chemical fertilizer enhances agronomic effectiveness of both by reducing the amount of fertilizer and improving the quality of compost. The present study aimed to explore the potential of organic and chemical nutrient sources with their optimal application and integration for sustainable wheat production. Accordingly, waste fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 16 publications
3
34
1
1
Order By: Relevance
“…There is a renewed interest in organic manures, such as FYMs, composts, and poultry manure, as sources of plant nutrients. Numerous studies have been conducted both under laboratory and field conditions to access the N release capacity and N fertilizer value of these manures (Aulakh et al, 2000; Abbasi et al, 2007; Ahmad et al, 2008; Gopinath et al, 2008; Azeez and Van Averbeke, 2010). Concerted efforts have been tried to use these organic sources to provide the same amount of food with less fossil fuel‐based inorganic fertilizers.…”
mentioning
confidence: 99%
“…There is a renewed interest in organic manures, such as FYMs, composts, and poultry manure, as sources of plant nutrients. Numerous studies have been conducted both under laboratory and field conditions to access the N release capacity and N fertilizer value of these manures (Aulakh et al, 2000; Abbasi et al, 2007; Ahmad et al, 2008; Gopinath et al, 2008; Azeez and Van Averbeke, 2010). Concerted efforts have been tried to use these organic sources to provide the same amount of food with less fossil fuel‐based inorganic fertilizers.…”
mentioning
confidence: 99%
“…So, in the present study, yield obtained under only SWC or IF was less than with their integration as SWC'IF. For more effective and economical use of N fertilizer, Ahmad et al (2008) suggested integration of the N fertilizer at lower rates with N-enriched compost.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased recycling through N enriched composting can be an effective way to increase wheat yields and decrease dependence on synthetic N fertilizer (Ahmad et al, 2008). Increasing crop rotations with legumes to increase N fixation, which would be compatible with organic agriculture practices and recycling, would also be a way to decrease synthetic N use (Badgley et al, 2007).…”
Section: Food Securitymentioning
confidence: 99%